2016
DOI: 10.1016/j.drugalcdep.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and methadone treatment for opioid dependence by income, ethnicity and race of neighborhoods in New York City

Abstract: Background Geographic and demographic variation in buprenorphine and methadone treatment use in U.S. cities has not been assessed. Identifying variance in opioid maintenance is essential to improving treatment access and equity. Purpose To examine the differential uptake of buprenorphine treatment in comparison to methadone treatment between 2004 and 2013 in neighborhoods in New York City characterized by income, race and ethnicity. Methods Social area (SA) analysis of residential zip codes of methadone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 39 publications
6
101
0
Order By: Relevance
“…Cognitive behavioral therapy (Kumari et al, 2016; Moore et al, 2016) and contingency management (Ling et al, 2013) have previously shown effectiveness with community-based samples and may have potential – if culturally adapted to address the specific substance use and mental health needs of criminal justice-involved African American men. Finally, while medication-based interventions have shown some efficacy (Carroll & Weiss, 2017) and effectiveness (Damian et al, 2017), compared to Whites, African Americans are disproportionately underrepresented in pharmacotherapy studies (Hansen et al, 2016; Mitchell et al, 2016). More research is needed to assess the acute and long-term effectiveness of buprenorphine, methadone, and potential barriers in accessing related treatments among African American men re-entering the community from prison.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Cognitive behavioral therapy (Kumari et al, 2016; Moore et al, 2016) and contingency management (Ling et al, 2013) have previously shown effectiveness with community-based samples and may have potential – if culturally adapted to address the specific substance use and mental health needs of criminal justice-involved African American men. Finally, while medication-based interventions have shown some efficacy (Carroll & Weiss, 2017) and effectiveness (Damian et al, 2017), compared to Whites, African Americans are disproportionately underrepresented in pharmacotherapy studies (Hansen et al, 2016; Mitchell et al, 2016). More research is needed to assess the acute and long-term effectiveness of buprenorphine, methadone, and potential barriers in accessing related treatments among African American men re-entering the community from prison.…”
Section: 0 Discussionmentioning
confidence: 99%
“…It has responded to opioid overdose pharmaceutically: The buprenorphine/Suboxone prescription rate is higher on Staten Island than in any other borough (Hansen et al. ). Residents of the higher income South Shore neighborhoods fill out 69% of all buprenorphine prescriptions on the island (New York State Department of City Planning ).…”
Section: Background: the Dangers Of White Privilegementioning
confidence: 99%
“…Most buprenorphine patients are treated in private physician practices (Roman, Ducharme, & Knudsen, 2006; Fiellin, 2007; Barry et al, 2010; Stanton et al, 2006; Magura et al, 2007) and pay out-of-pocket (Kissin, McLeod, Sonnefeld, & Staton, 2006) or are privately insured (Andrews, D’Aunno, Pollack, & Friedmann, 2014). Studies mapping buprenorphine prescriptions in New York City, the U.S. city with the largest opiate dependent population, confirm higher prescription rates in high-income residential areas with low percentages of Black and Latino/a residents (Hansen et al, 2013; Hansen et al, 2016). …”
Section: Introductionmentioning
confidence: 97%